The Effect of Two Post-Space Preparation Techniques on the Seal of Resilon and Gutta-Percha Obturation Materials - Ashofteh Yazdi, Kazem; Razmi, Hasan; Ghabraei, Sholeh; Shokouhinejad, Noushin; Aligholi, Marzieh; Rahmani, Saeed (Iranian Endodontic Journal, 2010)
INTRODUCTION: The aim of this study was to compare the effect of post space preparation with Gates Glidden drills or hand files on the sealing ability of gutta-percha or Resilon obturation materials. MATERIALS AND METHODS: One-hundred and four single-rooted human teeth were instrumented and divided into four experimental groups (n=21 each) and two groups of positive and negative control (n=10). Forty-two roots of experimental groups were obturated with gutta-percha and Dorifill sealer; and 42 roots with Resilon/Epiphany self-etch using lateral compaction technique. Each gutta-percha or Resilon group was divided into two subgroups (n=21) and post-space prepared with either Gates Glidden drills or hand files and chloroform. After post space preparation, 5 mm of apical gutta-percha or Resilon was left intact. The whole system was sterilized with gamma-rays. Saliva leakage was tested using a split-chamber model. Specimens were monitored every 24 hours for 30 days. The data were analyzed using log-rank test and Cox regression analysis. RESULTS: There were no significant differences between the sealing ability of gutta-percha and Resilon. Furthermore, no significant difference was found between two different methods of post space preparation (P>0.05). CONCLUSION: Under the limitations of this ex vivo study, there were no significant differences between the sealing ability of Resilon and gutta-percha after post space preparation using Gates Glidden drills or hand files with the aid of chloroform.